2013
DOI: 10.1590/s0034-71672013000500010
|View full text |Cite
|
Sign up to set email alerts
|

Uso de medicamentos por pessoas idosas na comunidade: proposta de ação de enfermagem

Abstract: Objective of this study was to identify the socio demographic profile and drug use in elderly enrolled in a health unit and to propose nursing actions through identification of diagnoses and prescriptions related, focused on the use of drugs, targeted to these elderly. This descriptive study was conducted in a family health unit, in the state of Rio Grande do Sul, Brazil, with 97 elderly. For data collection it was used a structured form. The data were analyzed by descriptive statistics. it was used Risner's m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
8

Year Published

2015
2015
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 11 publications
0
11
0
8
Order By: Relevance
“…3 É pertinente ressaltar que, com o avançar da idade, ocorrem alterações na farmacodinâmica e farmacocinética que tornam os idosos mais propícios aos efeitos negativos da polifarmácia. 26,27,28 Nesta investigação, assim como em outras pesquisas, [19][20][21][22][23][24][25]29 os medicamentos que atuam no sistema cardiovascular foram os mais utilizados. Como as doenças cardiovasculares estão entre as principais causas de morbidade e mortalidade em indivíduos idosos, os medicamentos com ação nesse sistema orgânico têm sido amplamente prescritos.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…3 É pertinente ressaltar que, com o avançar da idade, ocorrem alterações na farmacodinâmica e farmacocinética que tornam os idosos mais propícios aos efeitos negativos da polifarmácia. 26,27,28 Nesta investigação, assim como em outras pesquisas, [19][20][21][22][23][24][25]29 os medicamentos que atuam no sistema cardiovascular foram os mais utilizados. Como as doenças cardiovasculares estão entre as principais causas de morbidade e mortalidade em indivíduos idosos, os medicamentos com ação nesse sistema orgânico têm sido amplamente prescritos.…”
Section: Discussionunclassified
“…Trata-se de um achado consistente e relevante, amplamente observado em robustos estudos epidemiológicos sobre uso de medicamentos e polifarmácia em idosos. 3,11,[19][20][21][22][23]25,29,30 Fase a esse resultado, esses trabalhos alertam para a atenção às condições crônicas de saúde e suas repercussões, tornando-se um problema de saúde pública também no cenário do atual inquérito.…”
Section: Discussionunclassified
“…In Brazil, approximately 80% of elderly persons living in the community use at least one type of medication 2,3 . The use of more than one drug is also a common practice among this group, and may lead to complications arising from adverse reactions 4 .…”
Section: Introductionmentioning
confidence: 99%
“…A study conducted with elderly residents of Goiânia, in the state of Goiás found an average of 3.63 medications per elderly, as well as a prevalence of polypharmacy of 26.4%, similar to the prevalence found in the present study. A higher prevalence was found in a municipality in the extreme south of Rio Grande do Sul (31.86%) 13 . A study carried out among elderly people attended by the FHS in the urban area of Recife, Pernambuco, identified a prevalence of polypharmacy of 11%, lower than that found in the present study 14 .…”
Section: Resultsmentioning
confidence: 83%